Pengaruh Pemberian Telur Ayam dan Buah Jeruk Terhadap Peningkatan Kadar Hemoglobin pada Remaja Dengan Anemia - Dhea Hamidah; Linda Amalia; Asih Purwandari Wahyoe Puspita (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia is a condition when hemoglobin levels are below normal, disrupting the oxygen supply to body tissues. This study aims to determine the effect of chicken egg and citrus fruit consumption on hemoglobin levels in adolescent girls with mild to moderate anemia at SMAN Darmaraja in 2025. This study used a quantitative approach with a quasi-experimental design and a one-group pretest-posttest design. A total of 30 adolescent girls who had hemoglobin levels between 8–11.9 g/dL were divided into treatment and control groups. The intervention was in the form of giving boiled chicken eggs and citrus fruit for six consecutive days. The results of the Wilcoxon test showed a significant increase in hemoglobin levels in the treatment group, while the control group did not experience significant changes. The Mann-Whitney test also showed a significant difference between the two groups after treatment. These results prove that consumption of chicken eggs and citrus fruit has a positive effect on increasing hemoglobin levels. The protein, iron, and vitamin content in both ingredients play an important role in improving hemoglobin levels. The implications of this study indicate that this simple food combination can be an alternative non-pharmacological nutritional therapy for adolescent girls with anemia..